2019
DOI: 10.1042/bsr20182405
|View full text |Cite
|
Sign up to set email alerts
|

Colonic electrical stimulation promotes colonic motility through regeneration of myenteric plexus neurons in slow transit constipation beagles

Abstract: Slow transit constipation (STC) is a common disease characterized by markedly delayed colonic transit time as a result of colonic motility dysfunction. It is well established that STC is mostly caused by disorders of relevant nerves, especially the enteric nervous system (ENS). Colonic electrical stimulation (CES) has been regarded as a valuable alternative for the treatment of STC. However, little report focuses on the underlying nervous mechanism to normalize the delayed colonic emptying and relieve symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Duodenal electrical stimulation has been shown to reduce food intake, elevate plasma GLP-1, and improve glucose tolerance ( 31 , 32 ). Colonic electrical stimulation can potentially reduce inflammation and accelerate colonic transit time ( 33 , 34 ). Future work could explore how mucosally delivered stimulation might similarly affect neural and hormonal circuits in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Duodenal electrical stimulation has been shown to reduce food intake, elevate plasma GLP-1, and improve glucose tolerance ( 31 , 32 ). Colonic electrical stimulation can potentially reduce inflammation and accelerate colonic transit time ( 33 , 34 ). Future work could explore how mucosally delivered stimulation might similarly affect neural and hormonal circuits in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…We infer that vesicles play a role in STC. 21 Abnormal signal transduction is also involved in the pathogenesis. Progesterone interacts with progesterone receptor B (PGR-B), a G protein-coupled receptor, to impair muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Pulse train CES was also more efficient than long-pulse CES or short-pulse CES in [ 58 ], where they showed that with this modality, colonic motility was promoted by the regeneration of myenteric plexus neurons in STC beagles.…”
Section: Colonic Electrical Stimulation (Ces)mentioning
confidence: 99%